2022
DOI: 10.1177/08919887221078559
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Depression, Anxiety, Posttraumatic Stress Symptoms, Insomnia, Pain, and Fatigue in Clinically Stable Older Patients With Psychiatric Disorders During the COVID-19 Outbreak

Abstract: Objectives The Coronavirus Disease 2019 (COVID-19) pandemic has profound negative effects on the mental health of clinically stable older patients with psychiatric disorders. This study examined the influential nodes of psychiatric problems and their associations in this population using network analysis. Methods Clinically stable older patients with psychiatric disorders were consecutively recruited from four major psychiatric hospitals in China from May 22 to July 15, 2020. Depressive and anxiety syndromes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 84 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…Studies have reported that adults older than 50 years report greater physical health problems, especially those with a diagnosis of depression (79). People with these comorbidities may present somatic and physiological symptoms that reinforce a greater degree of fatigue, lack of energy, and insomnia (80).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that adults older than 50 years report greater physical health problems, especially those with a diagnosis of depression (79). People with these comorbidities may present somatic and physiological symptoms that reinforce a greater degree of fatigue, lack of energy, and insomnia (80).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has been extensively described as a collective trauma, which has been associated with a global increase in PTSD symptoms in different population groups [3,7,[12][13][14][15]. Variations in PTSD symptom clusters have been revealed by different robust statistical methods [15,18,29,36], and they have been integrated in the most recent versions of the DSM [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, terrorizing images of the outbreak and fake information communicated by mass/social media have accelerated fear levels regarding the effects of the pandemic on home finance and availability of food and essential supplies; they also heightened psychological distress and intensified traumatic emotions in the general public [2,10,11]. In this respect, many studies report higher occurrence of psychological trauma in COVID-19 survivors [3], healthcare workers [12], older adults (with psychiatric disorders) [13], adolescents and young adults [14,15], and even children [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, horrifying images of the pandemic and false/fake information frequently circulated in mass/social media have accelerated worries concerning the effects of COVID-19 on home finance and the availability of food and essential supplies; they also heightened psychological distress and to some extent intensified negative emotions/exaggerated fear responses to the pandemic in the general public [ 2 , 10 , 11 ]. In this respect, many studies report higher occurrences of psychological trauma in COVID-19 survivors [ 3 ], healthcare workers [ 12 ], older adults (with psychiatric disorders) [ 13 ], adolescents and young adults [ 14 , 15 ], and even children [ 7 ].…”
Section: Introductionmentioning
confidence: 99%